2012
DOI: 10.1111/j.1463-1326.2012.01626.x
|View full text |Cite
|
Sign up to set email alerts
|

Adiponectin increases insulin content and cell proliferation in MIN6 cells via PPARγ‐dependent and PPARγ‐independent mechanisms

Abstract: Our results identify novel roles for the adipokine, adiponectin, in β-cells function. Adiponectin upregulates PPARγ expression, insulin content and insulin secretion through PPARγ-dependent mechanisms. Reductions in circulating adiponectin levels in obese individuals could therefore result in negative effects on β-cell function and this may have direct relevance to β-cell dysfunction in type 2 diabetes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
30
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(31 citation statements)
references
References 49 publications
1
30
0
Order By: Relevance
“…Therefore, gAd may protect the liver from lipid accumulation by increasing insulin secretion and mediating glucolipid metabolism. Rao et al [18] suggested that adiponectin can increase insulin secretion, which was in agreement with our findings. Additionally, evidence has shown that gAd potentiates glucose-induced insulin secretion in both human pancreatic islets and rat beta cells via an AMPK-independent pathway [19] .…”
Section: Effects Of Gad On Insulin Receptor Protein Expression In LIVsupporting
confidence: 93%
“…Therefore, gAd may protect the liver from lipid accumulation by increasing insulin secretion and mediating glucolipid metabolism. Rao et al [18] suggested that adiponectin can increase insulin secretion, which was in agreement with our findings. Additionally, evidence has shown that gAd potentiates glucose-induced insulin secretion in both human pancreatic islets and rat beta cells via an AMPK-independent pathway [19] .…”
Section: Effects Of Gad On Insulin Receptor Protein Expression In LIVsupporting
confidence: 93%
“…In addition, it would be interesting to know if the anti-diabetic effect of adiponectin may also be involved in tissue preservation. Some data suggest that adiponectin regulates pancreatic cell growth [91]. In regards to this, we could wonder if adiponectin is involved in the preservation of integrity and functionality of the pancreas.…”
Section: Discussionmentioning
confidence: 99%
“…Adipose tissue is not only a site of energy storage [24], it is also a highly active and dynamic endocrine organ that synthesizes and secretes several adipose tissue hormones or adipokines including leptin, cytokines, adiponectin, complement components, plasminogen activator inhibitor-1, proteins of the renin-angiotensin system, and resistin [24]. Among these adipokines, adiponectin, visfatin, and omentin have previously been shown to be involved in obesity Infusion of adiponectin into the blood stream has been shown to decrease blood glucose levels and increase insulin sensitivity [7,34]. In hepatocytes, adiponectin decreases gluconeogenesis [49] and it increases fatty acid oxidation in both skeletal muscle [47] and hepatocytes [43].…”
Section: Introductionmentioning
confidence: 98%